Theobromine Does Not Affect Fasting and Postprandial HDL Cholesterol Efflux Capacity, While It Decreases Fasting miR‐92a Levels in Humans. Issue 13 (19th June 2018) - Talbot, Charlotte P.J.; Mensink, Ronald P.; Smolders, Lotte; Bakeroot, Virginie; Plat, Jogchum
Abstract : Scope: Chocolate consumption lowers cardiovascular disease risk, which might be attributed to the methylxanthine theobromine. These effects may be mediated through effects on HDL‐mediated cholesterol efflux, which may be affected by microRNA (miRNA) levels in the HDL particles. Therefore, the aim of this study is to investigate effects of theobromine consumption on fasting and postprandial cholesterol efflux and miRNAs levels. Methods and results: Thirty overweight and 14 obese healthy men and women participated in this randomized, double‐blind crossover study. Participants consumed 500 mg d −1 of theobromine or placebo for 4 weeks. ABCA1‐mediated cholesterol efflux was measured using J774 macrophages. MiRNAs levels (miR‐92a, miR‐223, miR‐135a*) were quantified in apolipoprotein B‐depleted serum. Theobromine consumption did not affect fasting and postprandial cholesterol efflux. Fasting miR‐223 and miR‐135a levels were unchanged, while miR‐92a levels were decreased (−0.21; p < 0.05). The high‐fat meal increased postprandial cholesterol efflux capacity (+4.3 percentage points; p ≤ 0.001), miR‐92a (+1.21; p < 0.001), and miR‐223 (+1.79; p < 0.001) levels, while a trend was found for miR‐135a (+1.08; p = 0.06). Conclusion: Theobromine did not improve fasting and postprandial ABCA1‐mediated cholesterol efflux capacity, but decreased fasting miR‐92a levels. High‐fat meal intake increased postprandial cholesterol efflux and the three selected miRNAs levels. Abstract : Daily consumption of 500 mg of theobromine does not change fasting and postprandial HDL‐mediated cholesterol efflux capacity, as well as fasting miR‐223 and miR‐135a levels. However, miR‐92a levels decrease after theobromine intake. Since miR‐92a is thought to be involved in angiogenesis and atherosclerosis, theobromine might exert beneficial effects. In addition, postprandial levels of miR‐92a, miR‐223, and miR‐135a increase 2 h after high‐fat meal consumption.